1999
DOI: 10.1172/jci4106
|View full text |Cite
|
Sign up to set email alerts
|

Patients with preeclampsia develop agonistic autoantibodies against the angiotensin AT1 receptor

Abstract: Preeclampsia usually occurs after week 20 of gestation and features hypertension and an increased peripheral vascular resistance. The mechanisms are unknown (1). Several lines of evidence implicate angiotensin II (Ang II) and its binding site, the AT 1 receptor. Preeclamptic patients manifest exaggerated pressor responses to Ang II. Gant et al. (2) infused Ang II into pregnant patients from week 10 of pregnancy onward and observed that those who later developed sustained hypertension required diminishing amou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
627
3
9

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 755 publications
(665 citation statements)
references
References 41 publications
14
627
3
9
Order By: Relevance
“…There were several speculations on the origin of AT 1 -AAs in previous works. In preeclampia, diminished placental perfusion could alter the AT 1 receptor expression in an aberrant fashion, thereby permitting autoantibody production (6). And in allograft renal-rejection subjects, posttransplantation reperfusion injury may alter the intragraft expression of AT 1 receptor, change its density, or cause conformational changes; a permissive environmental phenomenon might enhance local intragraft immunoreactivity owing to an activated innate immune response (33).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There were several speculations on the origin of AT 1 -AAs in previous works. In preeclampia, diminished placental perfusion could alter the AT 1 receptor expression in an aberrant fashion, thereby permitting autoantibody production (6). And in allograft renal-rejection subjects, posttransplantation reperfusion injury may alter the intragraft expression of AT 1 receptor, change its density, or cause conformational changes; a permissive environmental phenomenon might enhance local intragraft immunoreactivity owing to an activated innate immune response (33).…”
Section: Discussionmentioning
confidence: 99%
“…P1 corresponding to the second extracelluar loop of the human AT 1 receptor was used in the ELISA assay and preparation of the immunoglobulin (Ig) fractions. P2 corresponding to portion of the second extracelluar loop of the human AT 1 receptor was an epitope recognized by AT 1 -AAs from preeclamptic individuals (6), and was used in antibody neutralization experiment.…”
Section: Peptide Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…AT-1AA were purified and identified as belonging to a fraction of IgG antibodies. Wallukat et al (67) showed that AT1-AA bound to a certain seven amino acid sequence on the second extracellular loop of AT1-AA. They documented specificity by means of Western blotting and co-localization studies.…”
Section: Circulating Autoantibodiesmentioning
confidence: 99%